Jewelry : from antiquity to the present - Phillips, Clare (Illustrator) (New York : Thames and Hudson, 1997)
From the simple shell beads worn by Palaeolithic hunters to the splendor of Renaissance goldwork and the sumptuousness of Art Nouveau enamels, here is a fascinating and informative guide to the development of Western jewelry - concluding with the radical and experimental developments in the last three decades. Offering a concise survey of the entire field, this book analyzes jewelry's changing fashions, explores its social context, and examines how it has been worn by both men and women. It shows how jewelers have responded to new sources of gems, whether emeralds from the New World or diamonds from South Africa, and to the discovery of metals such as platinum and aluminum. Masterworks by unknown craftsmen and pieces designed by individual artists as diverse as Holbein, Pugin and Calder are illustrated alongside the glittering products of the major jewelry houses.
-- The ancient world -- Byzantium and early Europe -- The middle ages -- The Renaissance to 1630 -- Baroque to revolution -- Empire, historicism and eclecticism -- The Belle Epoque: diamonds, art nouveau, and the arts and crafts -- From art deco to the 1950s -- Since 1960.
Includes bibliographical references (pages 217-219) and index.
Keywords: Jewelry